Titanium steam turbine blading : workshop proceedings, Palo Alto, California, 9-10 November 1988 - Jaffee, Robert Isaac, 1917- (Electric Power Research Institute : Pergamon Press, 1990)
Application of titanium alloys to the long last stage and L-1 stage of low-pressure steam turbines has been in development for more than 30 years and now appears to be a commercial reality. Titanium blades are used in steam transition L-1 row because they are immune to pitting corrosion by the corrosive early condensates at the Wilson line. A disadvantage of titanium alloys is their low damping capacity, which requires blade designs that maximize mechanical and aerodynamic damping. Protection is not required in the L-1 row due to the water droplet erosion resistance of titanium alloys but the last stage rows operating at supersonic tip speeds require the use of erosion shields.